Prevalence of Stalking Among Justice Professionals in Portugal - Matos, Marlene (Journal of interpersonal violence, 2022)
Despite the growing interest from researchers? in recent years, stalking is a phenomenon of difficult operationalization within the scientific community. Examining the phenomenon in criminal justice professionals has become relevant since the work context is considered a fertile environment for the presence of stalking, despite underreported. This study aims specifically to know the prevalence, nature, dynamics, impact, and help-seeking behaviors (and its perceived effectiveness) of stalking victimization by criminal justice professionals stalked in Portugal. We were also interested in the professionals? perceptions of why they were stalked. The data were collected through a web-based survey, after the approval of the ethic committee. The sample was composed of 270 criminal justice professionals, mostly men (59.3%), with a mean age of 42.70 (SD = 9.07) years. The results showed that 24.8% reported having been stalked at least once in their lifetime. Stalking prevalence was higher in women compared to men. Concerning the profession, the highest prevalence was verified in the group of professionals composed of lawyers, jurists, court officials, and auditors, followed by the group of magistrates, and finally the judges and the criminal police. More diversity of stalking behaviors experienced was associated with a higher frequency of those behaviors. Psychological health (70.7%) and lifestyle/behavioral changes (62.1%) were the most reported areas of impact. Being stalked in a private context (e.g., intimate relationships), for a longer period and feeling a higher level of fear as a result of the stalking campaign were associated with more impact. Most of the victims (74.6%) revealed having sought help to cope with the stalking experience, with women seeking more help than men (88.6% vs. 59.4%). For bringing evidence that criminal justice professionals are at risk of being stalked, these findings can contribute to the adoption of policies and strategies to prevent stalking victimization among this population.